Development of E-Module with STEM Nuances to Improve Students' Creative Thinking Skills - Kurnia Wulansari; Irdawati; Abdul Razak; Moralita Chatri; Suci Fajrina (Jurnal Penelitian Pendidikan IPA, 2023)
One of the factors for improving the quality of education in schools is teaching materials. Based on the results of observations at SMAN 1 Sitiung that students have not used e-modules but use electronic teaching materials in the form of pdf files downloaded from the internet and only in the form of writing and a few pictures. Based on the results of the questionnaire, it is known that students have difficulty understanding the concept of the respiratory system material. This causes low student learning outcomes. Based on the results of the creative thinking questionnaire, it was found that students' creative thinking ability is still low with an average score of 33.8, so it is included in the less creative category. So it takes teaching materials that can help in visualizing the subject matter. This type of research is Plomp model development research which consists of three stages, namely the initial investigation stage, the development or prototyping stage, and the assessment stage. The research subjects were class XI students at SMAN 1 Sitiung for the 2022-2023 academic year. Validation results by the validator on nuanced e-modules Science Technology Engineering And Mathematics (STEM) shows an average grade 88.05% (very valid). Practical results by Biology teachers showed an average score of 87.5% (very practical) and 88.28% students (very practical). The test data for the effectiveness of creative thinking was obtained from the average essay questions 81.22% (very creative). Â